Joint interventions in osteoarthritis - Crema, Michel D.; Guermazi, Ali; Roemer, Frank Wolfgang (Skeletal Radiology, 2022)
Osteoarthritis (OA) is among the most common diseases affecting both axial and appendicular joints and the lead cause of disability worldwide. OA incidence is rising due to extended life expectancy and the increasing obesity epidemic. Several joint interventions are available to manage pain and joint function in patients with OA, most of these treatments being widely applied using intra-articular injections. In this chapter, we will describe the different joint interventions available for the management of pain in OA focusing on intra-articular injections, including discussion on the evidence regarding the efficacy of these treatments, based on the most recent systematic reviews and meta-analyses available. We also discuss the importance of imaging in guiding these treatments, including the different imaging modalities available for intra-articular injection guidance, their advantages, and disadvantages. Finally, we briefly discuss safety data and the consensus regarding the most used intra-articular treatments to manage pain in OA.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Corticosteroids; Imaging; Knee joint; Osteoarthritis; Platelet-rich plasma